Perancangan Sistem Informasi Penerimaan Trainee Baru Berbasis Web di Engima Camp - Raka Yudhistira; Nuraini Purwandari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research was conducted to design a new trainee acceptance system for Enigma Camp. Enigma previously used a conventional system where the process of accepting trainees was done manually, the obstacle of this system was that it was inefficient in time, cost and labor. The purpose of this research is to design a new web-based system that can be used for uploading trainee data, carrying out tests, and delivering results in one platform. The research method used is a prototype system development method with UML (Unified Modeling Language), Diagrams used in UML, namely: use case diagrams, activity diagrams, class diagrams, and sequence diagrams. The results of the study enable Enigma Camp to run the process of accepting trainees more easily, increase cost and labor efficiency, and reduce human error.